ANALISIS BENTUK KERJASAMA ANTARA MASYARAKAT LOKAL DAN TRANSMIGRASI DALAM PENYELESAIAN PEMBANGUNAN GEDUNG PAUD - Clara Octaviany; Yohanes Bahari; Gusti Budjang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThe title of this thesis is "Analyzing the Form of Cooperation between Local Communities and Transmigration in the Completion of PAUD Building Construction in Sebungkang Kelam Permai Sintang Village". A common problem in this research is "How is the form of cooperation between local communities and transmigration in the completion of PAUD building construction in Sebungkang Kelam Permai Sintang village" with the following sub-issues; 1) what are the forms of cooperation between local communities and transmigration in the completion of PAUD building construction in Sebungkang Kelam Permai Sintang village; 2) What are the factors which inhibiting the cooperation between local communities and transmigration in the completion of PAUD construction in Sebungkang Kelam Permai Sintang village; 3) What is the effort done by local communities and transmigration in the completion of PAUD building in Sebungkang Kelam Permai Sintang village. This research uses qualitative research method in the form of descriptive. Therefore, the tools of data collection in this research are observation checklist, interview and documentation. The results of this research showed 1) The form of cooperation between local communities and transmigration in the completion of PAUD construction is in the form of mutual cooperation and coalition cooperation; 2) The factors which inhibit the cooperation between local communities and transmigration in the completion of the construction of PAUD buildings were proven by difficulty dividing the work time and to support the family's needs; 3) The effort made by the communities in the completion of the construction of PAUD building is to provide material in the form of one sack cement requested from each family head. Key Words: Form of Cooperation, Local Communities, Transmigration